Maternal Periodontitis, Preeclampsia and Adverse Pregnancy Outcomes - Pourandokht Afshari; Shaghayegh Sheinizadeh; Ardeshir Rangbari; Foroogh khalilinejad (Mashhad University of Medical Sciences, 2013)
Background and Aim: Preeclampsia is a considerable problem of pregnancy. Endothelial dysfunction and placental hypoxia are the current hypothesis of preeclampsia. Chronic inflammation, including periodontitis may provoke systemic maternal and placental pro-inflammatory endothelial dysfunction, which represent a significant risk factor for diseases of vascular origin. So this study was carried out to evaluate the possible relationship between periodontitis and preeclampsia. Methods: A total of 360 pregnant women were included, corresponding to 180 pregnant women with mild or sever periodotitis in one group and 180 pregnant women with periodontal health in the other group. Periodontitis was determined by the sum of all pockets with pocket probing depth (PPD) ≥4mm and bleeding on probing. periodontal health was defined as the absence of PPD≥ 4mm. Then two groups evaluated to determine the presence of preeclampsia. After delivery, Child weight at birth and gestational age was also evaluated. Chi square and t test analysis were used to analyze the data. Results: There was statistically significant difference between two groups in presence of preeclampsia (p=0.003). Women who had a worse periodontal condition were at higher risk for preeclampsia. In addition, birth weight and gestational age was statistically lower in the case group than the control group (p < 0.001). Conclusion: The results indicate that the presence and severity of peridontitis increase the risk for occurrence of preeclampsia and adverse pregnancy outcomes.